PENGARUH KUALITAS LAYANAN INTERNET TERHADAP TINGKAT KEPUASAN NASABAH PERBANKAN DI DENPASAR - Alfonssius R. Paju (Journal of Business & Banking, 2011)
It is imperative to see whether the banks provide their customers satisfaction or not. This is acrucial thing for the banks. Therefore, it is also important to see what factors are consideredsignificant in terms of influencing the customers satisfaction. The purpose of this research isto explained influence of service quality towards customer satisfaction in internet bankingusers in Denpasar. There are six variables used to describe internet banking service such asquality, reliability, security, efficiency, responsiveness, access, and easiness to use. Theprocess of data collections by means of convenience sampling method by randomly taking allcustomers that have used internet banking in Denpasar. These customers are totaled 200internet banking users. The method analysis used in this research is linear regressionanalysis using the program SPSS 12.0. The results show that only reliability, efficiency, andeasiness to use have significant influence toward customer satisfaction of internet bankingusers in Denpasar. The management implication and suggestions for the banks as internetbanking service providers were also discussed at the end of this research